2016
DOI: 10.1103/physrevb.94.214205
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and criticality of the random anisotropy model in the large- N limit

Abstract: We revisit the thermodynamic behavior of the random-anisotropy O(N ) model by investigating its large-N limit. We focus on the system at zero temperature where the mean-field-like artifacts of the large-N limit are less severe. We analyze the connection between the description in terms of self-consistent Schwinger-Dyson equations and the functional renormalization group. We provide a unified description of the phase diagram and critical behavior of the model and clarify the nature of the possible "glassy" phas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…The nonperturbative FRG approach is also a versatile method that can be applied to the study of other disordered systems. This is for instance readily done for models with with a random mass 74 , random anisotropies 77,126 , for a disordered Bose fluid 129 , and for an elastic manifold in a random environment 130 . More generally, this can be carried out for any disordered model whose local order parameter is a simple field as magnetization, density or displacement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonperturbative FRG approach is also a versatile method that can be applied to the study of other disordered systems. This is for instance readily done for models with with a random mass 74 , random anisotropies 77,126 , for a disordered Bose fluid 129 , and for an elastic manifold in a random environment 130 . More generally, this can be carried out for any disordered model whose local order parameter is a simple field as magnetization, density or displacement.…”
Section: Discussionmentioning
confidence: 99%
“…4. Higher-order random anisotropies in O(N ) models in equilibrium 77,79,126 When the theory has an underlying continuous O(N ) symmetry, quenched disorder can take the form of random anisotropies that couple to products of field components. If these random anisotropies are only of even ranks, the model has an additional inversion symmetry compared to the random field model studied above in this article.…”
Section: Criticality In the Rfim In And Out Of Equilibrium 108mentioning
confidence: 99%
See 1 more Smart Citation
“…The more general relation between SD equations and 1-PI FRG flow will be analyzed elsewhere. 38 One can check that in the vicinity of the lower critical dimension for ferromagnetism, d = 4, the above equations coincide with the perturbative 1-PI FRG equations derived from the nonlinear sigma model. 7,9,13,25 Indeed in d = 4 + , the minimum of the effective potential, which corresponds to y k = 0, grows as ρ mk ∼ 1/ at and around the fixed point that controls the critical point.…”
Section: Cutoff-dependent Sd Equations and 1-pi Frg Flowmentioning
confidence: 63%
“…However only the case of D < 0 was of main interest in that study. Recent research of the large-m limit reported glassy character of zero-temperature state [54].…”
Section: A Theoretical Resultsmentioning
confidence: 99%